Efektivitas Pembiayaan tanpa Agunan Menggunakan Akad Murabahah pada Masa Pandemi Covid-19 di BTPN Syariah Kecamatan Hinai - Sri Safitri; Ahmad Fuadi; Khairunnisa (Institut Syekh Abdul Halim Hasan Binjai, 2022)
BTPN Syariah is a sharia bank that is expanding its segment by embracing and focusing segmentation on productive underprivileged customers in disbursing financing. According to Law N0.21 of 2008 concerning Islamic banking. Islamic bank is a bank that carries out its business activities based on sharia principles. One form of disbursement of funds by Islamic banks to the public is financing. In accordance with its commitment to providing financial literacy and empowerment activities for productive underprivileged customers, BTPN Syariah has a variety of funding and financing products that can help millions of families to grow and have a more meaningful life. One of them is the Right Syariah-Group Financing product which is specifically aimed at productive underprivileged women based on a wakalah wal murabahah contract whose focus is on building the character and good habits of customers. With the existence of the Right Syariah-Group Financing product, the community, especially mothers who are engaged in the Small and Medium Enterprises (SMEs) sector, find it helpful to increase the effectiveness of the businesses they have run. Therefore, Hinai District is one of the locations for the implementation of financing carried out by BTPN Syariah by providing financing to MSE players, especially mothers, to make business capital and capital for business development through financing funds from BTPN Syariah through sharia financing products. -group without collateral. The type of research used in this thesis is field research. Unsecured financing using a murabahah contract during the COVID-19 pandemic at BTPN Syariah, Hinai District is said to be effective, seen from the number of submissions or financing plans and the realization of the financing. During the COVID-19 pandemic, BTPN Syariah provided one-time payment relief for customers by canceling installment payments. In applying for unsecured financing using a murabahah contract during the covid-19 pandemic at BTPN Syariah, the customer does not have any problems, the prospective customer only provides a photocopy of his ID card and family card.